Investigation of the adsorption and degradation of metronidazole residues in agricultural wastewater by nanocomposite based on nZVI on MXene - Chen Chen; Wan Luo; Jinming Xu; Dongchun Niu (Alexandria Engineering Journal, 2023)
Metronidazole is a widely used antibiotic with powerful antimicrobial properties, but its presence in water can be detrimental to aquatic life and human health. To address this issue, we developed a novel composite material, zero-valent iron nanoparticles on alkalized Ti3C2Tx nanoflakes (NZVI/Ti3C2Tx), using an in-situ growth technique, aiming to efficiently adsorb and degrade metronidazole from aqueous solutions. The incorporation of Ti3C2Tx in NZVI/Ti3C2Tx resulted in enhanced dispersion, stability, and reactivity of NZVI. Our study demonstrated that NZVI/Ti3C2Tx exhibited the highest metronidazole removal efficiency (95.80%) within just 10 min of reaction time, outperforming NZVI and Ti3C2Tx alone. To optimize the removal process, we investigated the influence of various parameters on the degradation of metronidazole by NZVI/Ti3C2Tx, including the NZVI/Ti3C2Tx ratio, initial metronidazole concentration, pH, and reaction temperature. The highest removal rate was achieved with an NZVI/Ti3C2Tx ratio of 2:1 after 90 min of reaction time. As the initial concentration and pH of metronidazole increased, the removal efficiency decreased, while higher reaction temperatures improved the removal efficiency. Kinetic studies revealed that the degradation of metronidazole by NZVI/Ti3C2Tx followed a modified second-order parameter pseudo-first-order kinetic model, highlighting the effective reduction reaction. The unique properties of MXene nanosheets and NZVI synergistically contributed to the enhanced removal performance, with NZVI/Ti3C2Tx acting as an efficient adsorbent and reducing agent. Uur findings demonstrate the potential of the NZVI/Ti3C2Tx nanocomposite as an efficient and eco-friendly approach for the removal of metronidazole from agricultural wastewater. The combination of NZVI and Ti3C2Tx offers enhanced removal efficiency and stability, making it a promising material for water purification and environmental applications.